Flouting of Gricean Maxims and Conversational Implicature in the Podcast Rio Meets Cristiano Ronaldo - Juan Felix Sirait; Nurma Dhona Handayani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Conversational implicature, as defined by Grice (1975), denotes a speaker's intended meaning that is conveyed implicitly, rather than explicitly, and must be derived by the recipient. Speakers often utilize oblique language, humour, exaggeration, or selective information in podcast interviews. Rio Meets Cristiano Ronaldo audio verbal implicatures are the focus of this investigation. Grice's Cooperative Principle and the four conversational maxims of quality, quantity, relation, and manner are used to discover maxim breaches that cause implicatures. This study used qualitative descriptive methods. Data collection involved transcribing a 42-minute YouTube audio video, identifying statements with implicit meanings, and evaluating them with the pragmatic identification method established by Sudaryanto (2015). Nine utterances had conversational implicatures, with Maxims of Quality and Quantity breaches dominating. In interviews with public personalities, conversational implicature appears to be crucial to meaning creation, indirect expressing of opinions, and media discourse civility.